TINDAKAN KEJAHATAN INTERNASIONAL (GENOSIDA) YANG DILAKUKAN ISRAEL TERHADAP PALESTINA - Azzahra, Nisfah; Hibar, Ujang; Hifni, Mohammad; Amelia, Yosi Lutfi (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
Genocide against Palestinians is a highly controversial statement and does not necessarily reflect a consensus in the international community or among legal experts. Genocide is defined by the 1948 UN Genocide Convention as acts committed with the intent to destroy, in whole or in part, a national, ethnic, racial or religious group. Several groups or individuals have claimed that Israel is involved in acts that could be considered genocide against the Palestinian people. Some of the arguments or actions put forward as evidence include the use of military force, construction of settlements, expulsion of residents, restrictions on movement, and military attacks that cause civilian casualties